Opportunities and Challenges of Bacterial Glycosylation for the Development of Novel Antibacterial Strategies - Yakovlieva, Liubov; Fülleborn, Julius A.; Walvoort, Marthe T. C. (Frontiers in Microbiology, 2021)
Glycosylation is a ubiquitous process that is universally conserved in nature. The various products of glycosylation, such as polysaccharides, glycoproteins, and glycolipids, perform a myriad of intra- and extracellular functions. The multitude of roles performed by these molecules is reflected in the significant diversity of glycan structures and linkages found in eukaryotes, prokaryotes and archaea. Importantly, glycosylation is highly relevant for the virulence of many bacterial pathogens. Various surface-associated glycoconjugates have been identified in bacteria that promote infectious behavior and survival in the host through motility, adhesion, molecular mimicry and immune system manipulation. Interestingly, bacterial glycosylation systems that produce these virulence factors frequently feature rare monosaccharides and unusual glycosylation mechanisms. Owing to their marked difference from human glycosylation, bacterial glycosylation systems constitute promising antibacterial targets. With the rise of antibiotic resistance and depletion of the antibiotic pipeline, novel drug targets are urgently needed. Bacteria-specific glycosylation systems are especially promising for anti-virulence therapies that do not eliminate a bacterial population, but rather alleviate its pathogenesis. In this review we describe a selection of unique glycosylation systems in bacterial pathogens and their role in bacterial homeostasis and infection, with a focus on virulence factors. In addition, recent advances to inhibit the enzymes involved in these glycosylation systems and target the bacterial glycan structures directly will be highlighted. Together, this review provides an overview of the current status and promise for the future of using bacterial glycosylation to develop novel antibacterial strategies.